Motor neurone disease. Issue 923 (1st September 2002) - Talbot, K
Abstract : Motor neurone disease (MND), or amyotrophic lateral sclerosis (ALS), is a neurodegenerative disorder of unknown aetiology. Progressive motor weakness and bulbar dysfunction lead to premature death, usually from respiratory failure. Confirming the diagnosis may initially be difficult until the full clinical features are manifest. For all forms of the disease there is a significant differential diagnosis to consider, including treatable conditions, and therefore specialist neurological opinion should always be sought. Clear genetic inheritance has been demonstrated in a minority of patients with familial ALS but elucidation of the biological basis of genetic subtypes is also providing important information which may lead to treatments for sporadic forms of the disease. In the absence of curative or disease modifying therapy, management is supportive and requires a multidisciplinary approach. If, as seems likely, complex inherited and environmental factors contribute to the pathogenesis of MND, future treatment may involve a combination of molecular based treatments or restoration of cellular integrity using stem cell grafts.